Non‐Trivial Topological States in Spin‐Polarized 2D Electron Gas at EuO–KTO Interface with the Rashba Spin Texture - Sonali Kakkar; Chandan Bera (Advanced Physics Research, 2023)
Abstract Oxide heterointerfaces are gaining popularity for a variety of applications because of a wide range of emergent quantum phenomena. The creation of a highly conducting and spin‐polarized 2D electron gas (2DEG) with anomalous Hall effect at the EuO–KTaO3 (KTO) interface is reported by Zhang et al. (Phys. Rev. Lett. (2018), 121, 116803). The spin‐polarized 2DEG at the interface in EuO/KTO superlattice with a comprehensive electronic structure calculation using density functional theory (DFT) is investigated. It is shown that the magnetic ordering at the interface is related to the occupation of dxy orbitals of interfacial Ta. The band‐crossing points between the majority and minority spin states open a gap when spin–orbit coupling (SOC) is turned on. The large spikes of the Berry curvature Ω(k) at the momenta of spin–orbit (SO) gaps and integral Chern number demonstrate the non‐trivial band topology. As the system remains metallic, it can display quantum anomalous Hall (QAH) insulating characteristics possibly via strain engineering. The spin texture of the bands with the SO gap on constant energy contour displays single spin winding of electron spin with opposite chirality. The magnetic easy axis is perpendicular to the interfacial plane. Hence, our findings suggest that EuO/KTO system has potential in low‐power quantum electronics, spintronics, and spin‐orbitronics.